The Process of Team Building Among Content Experts and Methodologists: An Example From an Emergency Medical Services Research Investigation Kick-Off Meeting. (11th November 2020) - Guetterman, Timothy C.; Abir, Mahshid; Nallamothu, Brahmajee K.; Fouche, Sydney; Nham, Wilson; Nelson, Christopher; Mendel, Peter; Forbush, Bill; Shields, Theresa A.; Setodji, Claude M.; Hsu, Antony P.; Domeier, Robert M.; et al.
Background: Community-engaged research engages the community in a collaborative manner to improve the local setting and has been increasingly applied to health services research. These complex studies require collaboration and team building among clinical experts, methodologists, and community stakeholders, yet few examples of this process have been published. Aim: Through a study of community emergency medical services, our aim was to understand team building among content experts and methodologists to advance the framework for adaptive community-engaged research. Methods: We collected process field notes and transcripts from the project kick-off meetings and analyzed the data using an immersion/crystallization process, which is an exploratory qualitative analysis characterized by continual review of the data collected. All 25 members of the study's research team, who are both local to Michigan and reside out-of-state, were invited to attend. Results: We describe the process of the kick-off event for this community-engaged study and report major themes: collaborating throughout each stage of the kick-off meeting, building trusting relationships by challenging each other's perspectives and sharing expertise, and gaining shared experiences of learning and understanding of study content and goals. Conclusion: Team-building in community engaged health research requires thoughtful effort, and planned kick-off meeting can be a useful strategy to build a shared vision among content experts and methodologists.